Juvenile polyposis of the stomach: clinicopathological features and its malignant potential. Issue 9 (September 1997) - Hizawa, K; Iida, M; Yao, T; Aoyagi, K; Fujishima, M
Abstract : AIMS: To clarify a clinical entity of juvenile polyposis of the stomach compared with generalised juvenile gastrointestinal polyposis. METHODS: The clinicopathological features of juvenile polyposis dominantly involving the stomach at initial presentation were reviewed in 12 patients (three new patients and nine from the literature). These were compared with 29 cases of generalised juvenile gastrointestinal polyposis. RESULTS: There were three men and nine women with juvenile polyposis of the stomach, aged 10-63 years. Hypoproteinaemia was present in nine patients, anaemia in seven, and a family history of intestinal polyposis in seven. No patient presented with a congenital abnormality. During the observation period, two patients developed colonic juvenile polyps. Gastric polyps invariably affected the antrum and extended to the fundus, eventually becoming more numerous, larger, and more pedunculated. Ten patients required gastrectomy for associated malignancy or uncontrolled protein losing gastropathy. Histological examinations of the resected specimens demonstrated neoplastic tissue arising from juvenile polyps in four of the 12 patients. Atypism in these mixed polyps varied from adenoma to well or moderately differentiated adenocarcinoma. CONCLUSIONS: Juvenile polyposis of the stomach has malignant potential, and may be a separate entity from generalised juvenile gastrointestinal polyposis.